Recent advances in organic fluorophores as anti-counterfeit agents: an up-to-date review - N Akshaya; Annette Thomas; Glanish Jude Martis; Santosh L. Gaonkar (Discover Applied Sciences)
Abstract The problems of counterfeiting and duplicating valuable products such as confidential papers, banknotes, passports, nationality cards, and other vital documents have been increased exponentially. This poses a major challenge for companies, governments and for customers as well. According to a report published in 2017, the market for counterfeiting was found to be 107.26 billion dollars annually which increased to 206.57 billion dollars in 2021. Researchers are constantly looking for various strategies to effectively combat the problem of counterfeiting. Fluorescent molecules such as stimuli-responsive molecules, aggregation induced emission (AIE) luminogens such as tetraphenylethylene (TPE), heterocyclic complexes and photochromic-infused nanoparticles have been used to develop efficient security inks with maximum security and quick authentication. This review discusses various types of organic fluorophores used for developing safe inks and anti-counterfeit labels in recent years. This would help researchers in this field choose and design suitable molecules or derivatives for developing solutions for counterfeiting practices. Graphical Abstract